Application Of Multiple-Based Methods In Valuation Of Real Estate Development Companies - Żelazowski Konrad (Real Estate Management and Valuation, 2015)
The enterprise's market value is one of the main parameters characterizing the condition of the business entity, its development prospects and market position. It is an important criterion considered by managers and investors. Among the wide group of business valuation methods, multiple-based methods of valuation can be distinguished. Their undeniable advantage is the relative simplicity and speed of carrying out the process of valuation. An important condition for their application is a sufficiently developed and mature capital market.